Comparative Genomics of Early-Diverging Mushroom-Forming Fungi Provides Insights into the Origins of Lignocellulose Decay Capabilities. (10th December 2015) - Nagy, László G.; Riley, Robert; Tritt, Andrew; Adam, Catherine; Daum, Chris; Floudas, Dimitrios; Sun, Hui; Yadav, Jagjit S.; Pangilinan, Jasmyn; Larsson, Karl-Henrik; Matsuura, Kenji; Barry, Kerrie; et al.
Abstract: Evolution of lignocellulose decomposition was one of the most ecologically important innovations in fungi. White-rot fungi in the Agaricomycetes (mushrooms and relatives) are the most effective microorganisms in degrading both cellulose and lignin components of woody plant cell walls (PCW). However, the precise evolutionary origins of lignocellulose decomposition are poorly understood, largely because certain early-diverging clades of Agaricomycetes and its sister group, the Dacrymycetes, have yet to be sampled, or have been undersampled, in comparative genomic studies. Here, we present new genome sequences of ten saprotrophic fungi, including members of the Dacrymycetes and early-diverging clades of Agaricomycetes (Cantharellales, Sebacinales, Auriculariales, and Trechisporales), which we use to refine the origins and evolutionary history of the enzymatic toolkit of lignocellulose decomposition. We reconstructed the origin of ligninolytic enzymes, focusing on class II peroxidases (AA2), as well as enzymes that attack crystalline cellulose. Despite previous reports of white rot appearing as early as the Dacrymycetes, our results suggest that white-rot fungi evolved later in the Agaricomycetes, with the first class II peroxidases reconstructed in the ancestor of the Auriculariales and residual Agaricomycetes. The exemplars of the most ancient clades of Agaricomycetes that we sampled all lack class II peroxidases, and are thus concluded to use a combination of plesiomorphic and derived PCW degrading enzymes that predate the evolution of white rot.